Adolescent medial epicondyle trash lesion clinic radiological evaluation and treatment - Ghantasala, Navaneeth; Chokkalingam, Sitsabesan; ., Shibusumanth; Nair, Nikhilesh (International Journal of Research in Orthopaedics, 2022)
Elbow injures in children accounts for 10% of all fractures, ranges from simple sprain to elbow fracture dislocation. Ligamentous injury accounts for 2-3% only and are mostly sports related seen in overhead athletes. Trash lesions (the radiological appearances seemed harmless) around the elbow are reported in children under 10 years which are high energy trauma with initial normal looking X-rays. These are osteochondral or physical injures presenting with soft tissue swelling without any fractures. A high index of suspicion, early additional imaging such as MRI, CT scan, ultrasound examination and aggressive surgical care are usually necessary for prompt diagnosis and successful treatment of these injuries before complications arise. We presented a case of an elbow injury in a 15 year old girl, following a fall on her outstretched hand with initial normal findings in her X-rays. 3 months following the injury she had persisting pain and instability with ulnar nerve impingement symptoms. Her elbow CT scan, nerve conduction study confirmed the avulsion fracture of medial epicondyle with ulnar nerve neuritis and cubital tunnel syndrome. Valgus stress test proved the extent of additional medial instability. Medial epicondyle avulsion fractures are always challenging for fixation. The retracting UCL forces prevents healing and were prone for failure with non-operative splinting once instability is defined. Attempted fixation can also result in failure of fixation. Our case study highlights the possibility of such trash lesion in adolescent and also the modified technique of ulnar collateral ligament (UCL) reconstruction in a cost effective manner.